Template GNL-assisted synthesis of porous Li1.2Mn0.534Ni0.133Co0.133O2: towards high performance cathodes for lithium ion batteries - Huang, Y.; Hou, X.; Ma, S.; Zou, X.; Wu, Y.; Hu, S.; Shao, Zongping; Liu, X. (Royal Society of Chemistry, 2015)
Modified porous spherical Li1.2Mn0.534Ni0.133Co0.133O2 has been successfully synthesized via a co-precipitation method, adopting graphene and carbon nanotube conductive liquid (GNL) as a template and surface modified material. The unique porous structure and the larger specific surface area of the porous Li1.2Mn0.534Ni0.133Co0.133O2 contribute to both the increase in the first coulombic efficiency, from 76.3% to 82.0%, and the enhancement of the rate capability, demonstrating initial discharge capacities of 276.2, 245.8, 218.8, 203.9, 178.8, 135.9 and 97.5 mA h g−1 at different discharge rates of 0.1, 0.2, 0.5, 1.0, 2.0, 5.0 and 10 C, respectively. Even after suffering 100 cycles of charge–discharge, the porous Li-rich cathode can still deliver a discharge capacity of 235.5 mA h g−1, suggesting a high capacity retention of 86.2% compared to the initial discharge capacity (273.3 mA h g−1). Besides, the diffusion coefficient of the Li+ investigated by the cyclic voltammetry technique is approximately 10−12 cm2 s−1, indicating faster kinetics of the lithium ions for the modified porous Li1.2Mn0.534Ni0.133Co0.133O2 compared with the ordinary Li1.2Mn0.534Ni0.133Co0.133O2 (∼10−13 cm2 s−1). In fact, the introduction of GNL as a template not only leads to the porous structure of the Li-rich cathode material but also brings about improvement to the crystallinity and size of the grains, which can be ascribed to the combined effect of the GNL with the carbonate precursors of MCO3 (M = Mn, Ni, Co) during the recrystallization process.